Buck converter optimization using P&O algorithm for PV system based battery charger - Zainul Abidin; Adharul Muttaqin; Eka Maulana; M. Gilang Ramadhan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In this research, battery charger based on Photovoltaic (PV) system consists of buck converter as useful PV module interface was fabricated. Since output power of PV module changes quickly due to changing solar radiation, optimization is required. One of the easy and cheap optimization techniques is by implementing Perturb and Observe (P&O) algorithm for controlling switch of the buck converter. The P&O algorithm tracks maximum power point by generating suitable duty cycle for switching of the buck converter. The objective of this paper is to present the experimental proof of the P&O algorithm implementation in optimizing performance of the buck converter. The experimental results prove that the P&O algorithm can optimize the work of the buck converter and support shorter charging time by producing higher output voltage and power.